Cardio- and reno-protective effect of remote ischemic preconditioning in patients undergoing percutaneous coronary intervention. A prospective, non-randomized controlled trial - Ayman K.M. Hassan; Hamdy Shams-Eddin; Mona H.M. Abdel-Rahim; Heba A. Abd El-Hafeez; Sadat Edroos (The Egyptian Heart Journal, 2015)
Objectives: This study assessed the cardio- and renoprotective effect of remote ischemic Preconditioning (PreC) in patients undergoing percutaneous coronary intervention (PCI). Background: Myocyte necrosis and contrast induced nephropathy (CIN) occur frequently in PCI and are associated with subsequent cardiovascular events. Methods: Two hundred consecutive patients undergoing elective PCI with normal baseline troponin-I (cTnI) values were recruited. Subjects were systematically allocated into 2 groups: 100 patients received PreC (created by three 5 min inflations of a blood pressure cuff to 200 mmHg around the upper arm, separated by 5 min intervals of reperfusion) <2 h before the PCI procedure, and control group (n = 100). Results: The incidence of PCI-related myocardial infarction (MI 4a) at 24 h after PCI was lower in the PreC group compared with control group (41% vs 64%, P = 0.02). Subjects who received PreC had significant trend toward lower incidence of CIN at 72 h after contrast exposure (4 vs. 11, P = 0.05) and less chest pain during stent implantation compared to control group. At 3 months, the major adverse event rate was lower in the PreC group (6 vs. 14 events; P = 0.04). Conclusions: The use of PreC < 2 h before PCI, reduces the incidence of PCI-related MI 4a, tends to decrease the incidence of CIN and improves ischemic symptoms in patients undergoing elective PCI. The observed cardio- and renoprotection appears to confer sustained benefit on reduced major adverse events at 3 month follow-up beyond what is seen with judicious pre- and post-hydration (ClinicalTrials.gov identifier: NCT02313441).